Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning. (1st July 2021) - Castillo Vardaro, Jessica A.; Bonachela, Juan A.; Baker, Christopher C. M.; Pinsky, Malin L.; Doak, Daniel F.; Pringle, Robert M.; Tarnita, Corina E.
Abstract: Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems. Abstract : We coupled empirical and theoretical approaches to explore how competition and resource distribution interact to govern large‐scale spatial pattern formation by social‐insect ecosystem engineers. Data on East African fungus‐farming termites showed that individuals from different colonies fought fiercely, and that inter‐colony distances were greater when nests were large and resources scarce, consistent with strong intraspecific competition. A dynamical model of competitive interactions on different substrates provided novel mechanistic insight into the roles of resource availability and heterogeneity in modulating pattern regularity and its emergent effects on system‐wide productivity.